Modeling of Turbulent Non-Isothermal Flow in a Heating Network Pipe - Zhapbasbayev, U.K.; Bossinov, D.Zh.; Pahomov, M.A.; Sattinova, Z. (Karagandy University of the name of academician E.A. Buketov, 2025)
The article presents a mathematical model of turbulent non-isothermal flow of viscoplastic fluid in a pipe with a sudden expansion of the heat network. Heat exchange of non-isothermal flow of viscoplastic fluid with cold environment leads to an increase in its viscosity and yield strength. Shvedov-Bingham rheological model represents the viscoplastic state of fluid. The Reynolds Stress Model (RSM) turbulence model describes the properties of anisotropy of the velocity components of pulsating motion in a pipe with a sudden expansion. In addition, the ability to predict turbulence anisotropy of the RSM model is used to construct a linear model of turbulent viscosity. Calculation data are obtained for different values of Reynolds and Bingham numbers. The calculation results show that with an increase in the Bingham number, the circulation zone decreases behind the section of the sudden expansion of the pipe. The results of the comparison of the radial profiles of the normalized axial mean and fluctuation velocity with the experimental data along the pipe with sudden expansion are given. The results show the anisotropic property of the axial and radial profiles of the velocity of fluctuation movement, which are in agreement with the data of the DNS (Direct Numerical Simulation) model.
Жылу желісі кенеттен кеңейгенде құбырдағы тұтқырпластикалы сұйықтықтың турбулентті ағынын модельдеу
Моделирование турбулентного течения вязкопластичной жидкости в трубе тепловой сети с резким расширением
Keywords: sudden expansion pipe; non-isothermal turbulent flow; viscoplastic fluid; RSM model of turbulence; yield strength; heat transfer; recirculation region; fluctuation velocity